Digital transformation management of SMES in Ukraine under martial law - Ozorovych, Andriy; Matsola , Mykhailo (Management and Entrepreneurship: Trends of Development, 2026)
The purpose of this article is to explore the current state and key barriers to digital transformation of small and medium-sized enterprises (SMEs) in Ukraine under conditions of full-scale war. It analyses the impact of security, financial, human resource, and infrastructure constraints on firms’ capacity for technological renewal, highlighting that limited access to capital, skilled workforce shortages, and high uncertainty significantly narrow the planning horizon for Ukrainian SMEs. Methodology: The study relies on desk research, official statistics, policy documents, and international as well as national indices of digital maturity to identify structural factors that shape the pace and direction of SME digitalisation. Particular attention is paid to the paradoxical combination of high public sector digitalisation and relatively low average digital maturity of SMEs, which produces an asymmetric environment of opportunities and constraints. Findings of the study reveals that state digital ecosystems such as Diia and Diia.Business function as instrumental support platforms that reduce transaction costs, expand access to financial and advisory instruments, and facilitate the formalisation and scaling of entrepreneurial activity. On this basis, the paper conceptualises hybrid digital infrastructure as a core element of digital resilience that integrates cloud services, backup connectivity channels, and autonomous power systems to support business continuity under conditions of physical, cyber, and energy insecurity. The empirical generalisations allow the authors to systematise typical strategies of wartime digital adaptation for Ukrainian SMEs, including step-by-step digital transformation, intensive use of state e-services, development of digital competences within firms, and risk-oriented investments with short payback periods.JEL Classification: O32, O33, L26, L53